(untitled) (Ustozlar uchun, 2025)
This article explores the effectiveness of interactive teaching methods in teaching English compound sentences to A2 level students. Compound sentences are often challenging for learners at this level due to their limited grammatical knowledge. The study emphasises the use of pair work, group activities, games, and communicative tasks to help students understand and use compound sentences correctly. The article highlights how interactive methods increase learners’ motivation, participation, and grammatical accuracy. The findings suggest that interactive teaching methods significantly improve students’ understanding of compound sentence structures.V